The Effect of Grazing Level and Ageing Time on the Physicochemical and Sensory Characteristics of Beef Meat in Organic and Conventional Production - Isabel Revilla; Javier Plaza; Carlos Palacios (Animals, 2021)
This study investigated the influence of the production system (conventional vs. organic), the grass consumption level and the ageing period (7 and 14 days) on beef quality. Three groups of samples from Limousin × Avileña calves were analysed: F100, formed by animals fed 100% on forage; F74, formed by animals fed on an average amount of forage of 74%; and F35, formed by animals fed on straw fodder (35%) and concentrate (65%). The results showed that the higher the grass content, the lower the fat oxidation and the higher the n-3 content, but also the higher the SFA level, the initial Warner-Bratzler shear force (WBSF), and the more residue it leaves on chewing. As for the effect of production system, organic samples showed higher intramuscular fat content and lower moisture and MUFA content. These samples were darker and showed lower values for flavour quality. Among the organic samples, F100 had higher n-3 and CLA content and higher values for colour, hardness, odour and flavour quality. Increased ageing time may improve the sensory characteristics of the meat, especially in the case of the F100 samples. The results pointed out that F100 samples aged at least 14 days showed the best physico-chemical, nutritional and sensory characteristics.